Operational resilience in the business-battle space - Matthews, Ron; Ansari, Irfan; Watters, Bryan (Capco Institute, 2021)
The purpose of this paper is to explore the interconnectivity between defence, security, and business, particularly when viewed through the prism of operational resilience. The standard stereotype depicts the military acting as a harbinger of destruction while business represents the motive force of wealth generation. This is too simplistic, however. Militaries fight wars, but they also make an important contribution to addressing the expanding array of non-traditional threats that form part of national security, including wildfires, floods, earthquakes and, of course, pandemics, such as COVID-19. The military’s physical resources, attitudinal robustness, and rigorous planning regimes represent three of the more important dimensions of military operational resilience. Mutual commercial-military benefits can be gained via a “two-way” street in the adoption of best-practice resilience solutions. There is a recognition that just as military resource managers can learn from business, so equally can business learn from the military. The U.K. case is offered to illustrate the principles, policies, and practices of military operational resilience.